Atmospheric warming threatens the untapped glacial archive of Ortles mountain, South Tyrol - Gabrielli Paolo; Carturan Luca; Gabrieli Jacopo; Dinale Roberto; Krainer Karl; Hausmann Helmut; Davis Mary; Zagorodnov Victor; Barbante Carlo; Dalla Fontana Giancarlo; Thompson Lonnie; SEPPI, ROBERTO (Journal of Glaciology, 2010)
Ortles mountain (3905m a.s.l.), South Tyrol, Italy, is the highest mountain of the Eastern European Alps, and its upper glacier, Alto dell’Ortles, presents a unique opportunity to obtain the first paleoenvironmental record from an ice core in this area. To study the suitability of this glacier as a drilling site, in 2009 we performed the first preliminary study of its glaciological characteristics at _3830ma.s.l. The maximum thickness is _75 m, and lamination of the exposed ice layers is excellent down to bedrock. Firn and ice lenses were observed in a 10m shallow core, and the firn/ice transition was below _24 m. The seasonal chemical signal is clearly preserved only within the uppermost 2008 and 2009 snow/firn. A simple mass-balance model, the incipient ‘smoothing’ of the chemical record, and the observed ice lenses provide evidence that melting, infiltration and refreezing cycles occurred within the firn layers formed before 2008. Nevertheless, the mass balance of the upper part of Alto dell’Ortles was positive (_800mma–1) during the last few years. We suggest that an environmental history is likely to be well preserved only within the ice layers formed before _1980, when summer air temperature was _28C colder than today in this area. Clearly the continued warming trend predicted to occur over the next few decades, and the consequent increase in frequency and/or intensity of infiltration processes, will endanger the preservation of the glacial archive conserved in the deep ice layers of Ortles mountain.